Analisis Manajemen Laba, Penghindaran Pajak, Tata Kelola Terhadap Tanggung Jawab Sosial - Budi Harsono; Susanti Susanti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study focuses on explaining the correlation between earnings management, tax avoidance, and the mechanism of corporate governance of public listed companies on the Indonesia Stock Exchange (IDX). Disclosure of corporate social responsibility is the dependent variable tested, while the independent variables used include earnings management, tax avoidance, corporate governance and ownership structure. Company size and leverage are the control variables used in this test. This research was conducted using secondary data and panel regression methods. This study uses statistical programs such as SPSS and eviews. The research sample amounted to 2,160 data or equivalent to 432 companies listed on the Indonesia Stock Exchange in the 2014-2018 periods. The results of this study shows that the independent director variable, company size, leverage and foreign ownership had a significant effect, while earnings management, tax avoidance, managerial ownership, institutional ownership, the size of the board of directors and commissioners did not each have a significant effect on disclosure of corporate social responsibility.